The Relationship Between Body Image And Eating Patterns In Middle Adolescents In Public High School 05 Bengkulu City In 2024 - Sari, Ayu Permata; Metasari, Des; Susanti, Meri Epriana (CV. Utami, 2025)
Adolescents between the ages of 10 and 19 are faced with a triple nutritional burden with co-existence of undernutrition, overnutrition and micronutrient deficiencies. About a quarter of adolescents aged 13-18 years are stunted or short, 9 percent are underweight or have a low body mass index, while 16 percent are overweight and obese. In addition, about a quarter of adolescent girls experience anemia. The purpose of this study was to determine the relationship between body image and diet in middle adolescents at SMA Negeri 05 Bengkulu City in 2024.The research method used was descriptive quantitative research with a cross sectional approach. Sampling technique using simple random sampling technique with the number of samples in this study 77 people representing all students at SMA Negeri 05 Bengkulu City in 2024. The results showed that most of the respondents (59.7%) with negative body image, most of the respondents (50.6%) with poor diet. There is a relationship between body image and eating patterns in middle adolescents indicated by p=0.000. It is concluded that body image is determined by eating patterns in middle adolescents at SMA Negeri 05 Bengkulu City, so it is recommended for SMA Negeri 05 Bengkulu City the results of this study can be the basis for implementing guidance, coaching, and counseling activity programs on body image with eating patterns in middle adolescents.